Implementing A Cubeacon for Student Presence in Classroom - Oktaviana, Shinta; Apriliantari, Yesnida (POLITEKNIK NEGERI JAKARTA, 2019)
Student presence is an one of the important thing in academic activity especially in a university. Cubeacon is a bluetooth technology that can be implement for student presence purpose. It is low cost energy and easy to deploy. Cubeacon are used to record the position and the time of student presence. Student can monitoring their presence so students can keep their presence on the track. System are made in two platform, i.e. mobile android and website. API are made to connect each device. Firebase Cloud Messaging are use to send message from website to android device that are use for send notification. Website are built using Laravel as framework. PostgreSQL are use as database. Testing are done to see how the cubeacon can detect the device. The result are that smartphone can detect the cubeacon till 50 m distance when there is no barrier, can detect cubeacon till 20 m distance when the barriers materials are board, and can only detect cubeacon under 10 m distance when the barrier that is used is wall materials